The dynamic investigation of intrinsic vibration characteristics of a stranding machine by the finite element method - Ren, Kai; Leng, Bo; Zhang, Chang; Sun, Qingyun; Tang, Wencheng (Frontiers in Physics, 2023)
In response to the design problems of violent vibration and noise when the stranding machine is running at high speed, this project completes the motion simulation and vibration analysis of the stranding machine based on the prototype FB-650C-2 bow-type stranding machine produced by Fuchuan Mechanical and Electrical Technology Co. The modal analysis was carried out in ANSYS to obtain the first eight orders of inherent frequencies and vibration patterns; combined with the excitation force analysis to verify whether the rotating part can avoid the resonance frequency when working. Harmonic response analysis was carried out based on the modal state to calculate the steady-state forced vibration of the structure, and the variation curve of response value (usual deformation) with frequency and the cloud diagram of stress distribution of each component at the rotation frequency was obtained, and suggestions for improving vibration and reducing noise were made based on the experimental and analytical results.